A Simulated Study Of Smallholder Dairy Production Systems - Soetrisno, R. Djoko (1989)

(untitled)
Four experiments were conducted to investigate the productive performance of Sahiwal-Friesian cows under different feeding managements. Rotational grazing at stocking rate 6.25 milking cows ( AU ) / ha on Setaria splendida and stall- fed cut Panicum maximum ( Guinea grass ) both with high cost concentrate containing 5.0 % fish meal supplementations ( Experiment I) were done following split - plot in time design , followed by ( Experiment 11 ) comparing ( t-test ) the performance of cows grazed on splendida ( rotationally ) at low ( 4.0 AU/ha ) and high SR (8.0 AU / ha ) with low cost concentrate (LCF) supplementation for HSR group . A split - plot in time design was also used to determine the effect of type of concentrates formulated based on cost with cut Guinea grass on the performance of the cows ( Experiment III), and to evaluate the effect of machine milking with the presence and the absence of calves (Experiment IV).